(untitled) (Research, Society and Development, 2020)
The present work aimed to characterize and quantify four contaminants (ethyl carbamate, 2,3-butanedione, furfural and 5-hydroxymethylfurfural) present in still and industrial cachaça. The four contaminants ethyl carbamate, 2,3-butanedione, furfural (FU) and 5-hydroxymethylfurfural (5-HMF) were analyzed in spirits produced by alembic and column distillation. Forty-four samples of cachaça were collected in the southern, central-western, and southeastern regions of the state of Minas Gerais and in the state of São Paulo. The samples were subjected to chromatographic analysis. Ethyl carbamate, 2,3-butanedione, furfural and 5-HMF were characterized and quantified by HPLC. Two samples of spirits were found to contain concentrations of ethyl carbamate that were greater than the legal limits, ranging from 245.31 to 235.53 μg L-1. None of the alembic samples had concentrations higher than the legal limit. The spirits obtained by column disitllation contained higher concentrations of the 2,3-butanedione than the alembic liquors. An analytical method was developed and validated for the quantification of furfural and 5-HMF, and the spirits obtained by column distillation contained concentrations higher than the limit established by legislation.